2020
DOI: 10.1002/brb3.1699
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of probiotics on stress in healthy volunteers: A systematic review and meta‐analysis based on randomized controlled trials

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 84 publications
1
34
2
Order By: Relevance
“…demonstrated that psychological distress increased coronavirus infections in healthy subjects who were inoculated with either one of five respiratory viruses including coronavirus‐type 229E through nasal drops. Gut dysbiosis is well known to exist in chronically stressed individuals, 53 and probiotics have been used to relieve stress in clinical trials 54 …”
Section: Dysregulation Of the Intestinal Microbiota In Covid‐19mentioning
confidence: 99%
“…demonstrated that psychological distress increased coronavirus infections in healthy subjects who were inoculated with either one of five respiratory viruses including coronavirus‐type 229E through nasal drops. Gut dysbiosis is well known to exist in chronically stressed individuals, 53 and probiotics have been used to relieve stress in clinical trials 54 …”
Section: Dysregulation Of the Intestinal Microbiota In Covid‐19mentioning
confidence: 99%
“…Supplementation with Lactobacillus reuteri reduced stress-induced anxiety-like behaviours 30 and restored disturbed social behaviour in mice with an unbalanced gut microbiota 31 . Meta-analyses also suggest that probiotic supplementation in humans can reduce subjective stress levels without altering cortisol levels 32 and has antidepressant and anxiolytic effects 33 . One possible pathway by which Lactobacillus may influence the behaviour of its host is through the production of neurochemicals similar to those produced in vertebrate organisms 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a systematic review and meta-analysis of RCTs including 1146 volunteers revealed that probiotics can mitigate subjective stress, but more evidence from clinical trials is needed to confirm these results [52].…”
Section: Probioticsmentioning
confidence: 99%